2015
DOI: 10.1097/acm.0000000000000677
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Task-Evoked Pupillary Response as an Objective Measure of Cognitive Load in Novices and Trained Physicians

Abstract: Novices require more mental effort to answer clinical questions than trained physicians, even when both respond correctly. Measuring TEPRs has the potential to be a valuable assessment tool by providing objective measures of expertise and is worthy of further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 21 publications
5
74
0
Order By: Relevance
“…Essentially, the group with the lower intelligence had to "think harder" to achieve the same correct response as the group with higher intelligence. Moving away from intelligence defined by standardized testing, a study by Szulewski et al (2015) found similar results in novices and trained physicians as they answered clinically-based multiple choice questions. The participant groups in this study were divided not by intelligence, but by clinical experience.…”
Section: Pupillometry and Expertisesupporting
confidence: 48%
See 2 more Smart Citations
“…Essentially, the group with the lower intelligence had to "think harder" to achieve the same correct response as the group with higher intelligence. Moving away from intelligence defined by standardized testing, a study by Szulewski et al (2015) found similar results in novices and trained physicians as they answered clinically-based multiple choice questions. The participant groups in this study were divided not by intelligence, but by clinical experience.…”
Section: Pupillometry and Expertisesupporting
confidence: 48%
“…Anecdotally, cognitive efficiency seems to evolve with experience. The "anatomy" of working memory is thought to change with the development of expertise and it is likely that certain clinical tasks cognitively load experts and novices in different ways (Szulewski et al, 2015). This evolution of the thinking process is tied to expertise development.…”
Section: Pupillometry and Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been applied in medical education: Szulewski et al 30 showed that pupil dilation was greater when emergency medicine trainees answered difficult clinical questions as compared with easier questions. Pupil dilation, however, is much more sensitive to ambient lighting conditions than it is to cognitive load.…”
Section: Use Of Eye Tracking To Investigate and Optimise Instructionamentioning
confidence: 99%
“…For example, we use an eye tracker to define constantly occurring micro-movements of our eyes as a singular "fixation" and then study the frequency of fixations, their durations, or the time between fixation onset and the initiation of a movement (Panchuk, Vine, & Vickers, 2015). The underlying assumption is that visual expertise is an individual capacity that resides inside the mind or brain of an elite performer (Gruber, Jansen, Marienhagen, & Altenmueller, 2010; Seppänen & Gegenfurtner, 2012;Szulewski, Roth, & Howes, 2015). In recent years, there has been an increasing interest in studying the social and cultural sources that correspond with individual displays of expert performance (Gegenfurtner, Siewiorek, Lehtinen, & Säljö, 2013;Stoeger & Gruber, 2014).…”
Section: Introductionmentioning
confidence: 99%